A path for Chinese civil society : a case study on industrial associations in Wenzhou, China - Yu, Jianxing (Challenges facing Chinese political development., 2012)
Through close investigation into the industrial, organizational, and social governance of industrial associations in Wenzhou and in-depth analysis of their challenges and developments within the institutional context, this book explores the non-western path for civil society development in China and provides fresh empirical evidence and insightful analysis of how industrial associations have actively participated in local industrial governance and conduct of public affairs, gained greater space for their development, and become indispensable partners of local government in so.